Pengaruh Pemanfaatan Teknologi Informasi Dan Modernisasi Sistem Penerimaan Pajak Parkir Terhadap Kepatuhan Wajib Pajak Parkir Era Pandemi Covid-19 Di Badan Pengelola Pajak Dan Retribusi Daerah Kota Medan (Parkir Restaurant Kota Medan) - Putri Septiana Margaretha Zega; Rahmawaty Hasibuan; Rizka Hilda Siregar; Situmorang, Martalina; Eka Rizki Meiwinda; Tika Handayani; Ayu Kalista (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Parking tax compliance is a taxpayer's activity in implementing applicable tax provisions. Compliant Taxpayers are Taxpayers who comply with their tax obligations in accordance with the provisions of the Legislative Regulations (Siti Kurnia Rahayau, 2017). Based on data published by the Medan City Regional Tax and Retribution Management Agency Office, the higher the level of parking tax compliance, the higher the level of parking tax revenue which is supported by the information technology system and modernization of the parking tax revenue system. The aim of this research is to determine the influence of information technology, modernization of the parking tax revenue system on parking tax compliance at the Medan City Regional Tax and Retribution Management Agency in the era of the Covid-19 pandemic. The research method uses quantitative methods with primary data from the Medan City Regional Tax and Retribution Management Agency. The sampling method in this research uses the Probability Sampling method for the period 2017 to 2022, and has met the sample fulfillment criteria. The research results show that information technology and modernization of the parking tax revenue system have an influence on parking tax compliance.